PSYCHOLOGICAL CAPITAL AND ITS ROLE IN ENHANCING THE VOICE BEHAVIOR OF EMPLOYEES: AN ANALYTICAL EXPLORATORY STUDY FOR A SAMPLE OF WORKERS IN THE DIRECTORATE OF EDUCATION OF NAJAF GOVERNORATE IN IRAQ - Hamed A.Al- Nasrawi (Scholar Express Journal, 2023)
The current research seeks to know the nature of the relationship between psychological capital and voice behavior in the Directorate of Education of Najaf Governorate. Iraqi institutions, so the researcher used the random sample method and distributed 63 questionnaires to several male and female employees in the mentioned directorate. The number of retrieved questionnaires was 58, while the number valid for statistical analysis reached (58) with a response rate of (92%) of the retrieved questionnaires, and they were analyzed by the advanced statistical program Smart Plus, as well as the statistical program SPSS v.23. The theoretical results showed the existence of a knowledge gap to explain the relationship between psychological capital and voice behavior in organizations in general and in the Directorate of Education in particular
Keywords: psychological capital; voice behavior; the Directorate of Education in Najaf Governorate